Caminhos da docência: trajetórias de mulheres professoras em Sabará Minas Gerais (1830-1904) - Cecilia Vieira do Nascimento (2011)
This study aims to understand, in a historical perspective, the different ways of including women in elementary teaching, taking as reference a group of female teachers. During the nineteenth century, the presence of women in this occupation was gradually becoming more significant in the province of Minas Gerais, as it has happened in other provinces of Brazil and other Western nations. In Minas Gerais, according to recent studies, the inclusion of women in teaching does not seem to coincide with the current interpretation of historiography, for which women were allowed to teach through the Teacher Training Colleges, where teacher training rooms were set up on a larger scale around 1880. If not the Teacher Training Colleges, who was responsible to authorize the presence of women in this occupation, and who prepared the conditions that allowed women to enter the teaching profession? Those are the motivating questions of this study. In order to answer them, it is important to understand the paths of fourteen teachers who worked in different moments of the nineteenth century in the town of Sabará, Minas Gerais, an important region in the period, and in its surroundings. As a privileged strategy, we seek to understand the atmosphere related to a group of established teachers, as well their influences and thoughts: socio-cultural, labor, literature, family and normal school. It is noticed that during the nineteenth century there were a convergence of favorable aspects to the inclusion of women in teaching, as the networks of sociability were constructed and experienced by the study group. However, the social environment arising from the Catholic Church, the ambiance of the classroom as some students helped the teachers the press, the Teacher Training Colleges and, most prominently, influences built in the very familiar atmosphere, were responsible to make teaching a kind of intangible heritage.